2017
DOI: 10.13083/reveng.v25i2.728
|View full text |Cite
|
Sign up to set email alerts
|

Uso Do Índice S Na Avaliação Da Qualidade Físico-Hídrica De Solos Do Cerrado Matogrossense

Abstract: A qualidade físico-hídrica do solo influencia o potencial de uso, a produtividade e a sustentabilidade dos agroecossistemas, sendo seu estudo necessário para fornecer informações sobre o manejo do solo e assegurar a tomada de decisões para uma melhor utilização desse recurso. Para avaliar a qualidade físico-hídrica dos solos tem sido proposto o “índice S”, baseado no ponto de inflexão da curva de retenção da água no solo. Objetivou-se com esse trabalho avaliar a qualidade físico-hídrica de solos do cerrado matog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…According to Carducci et al (2011) and Silva et al (2012), the curve shape reflects the soil pores distribution by size, which is affected by the soil management. Jardini and Amorim (2017), studying some physical attributes of different soils (Ultisols, Oxisols, Inceptisols and Entisols Quartzipsamments), found in the state of Mato Grosso, Brazil, under distinct uses (pastures, sugarcane, corn, soybeans and without agricultural use) in the Cerrado biome, verified a positive correlation between the S index and the soil organic carbon content. Li et al (2011) also observed a positive association between the S index and the organic matter content of an Ultisol under different managements in the Southeast region of Australia, which contrasts with our results.…”
Section: Resultsmentioning
confidence: 81%
“…According to Carducci et al (2011) and Silva et al (2012), the curve shape reflects the soil pores distribution by size, which is affected by the soil management. Jardini and Amorim (2017), studying some physical attributes of different soils (Ultisols, Oxisols, Inceptisols and Entisols Quartzipsamments), found in the state of Mato Grosso, Brazil, under distinct uses (pastures, sugarcane, corn, soybeans and without agricultural use) in the Cerrado biome, verified a positive correlation between the S index and the soil organic carbon content. Li et al (2011) also observed a positive association between the S index and the organic matter content of an Ultisol under different managements in the Southeast region of Australia, which contrasts with our results.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, evaluating the physical-hydric quality of the soil is important to assess the potential of its use to ensure both food productivity as well as the sustainability of agroecosystems. Physical-hydric surveys are necessary to provide information on soil management, ensure decision-making for better use of this resource [86,87], and maintain water quality and sustainability in river basins [88]. Changes in land use can alter ecosystem services provided by the soil.…”
Section: Discussionmentioning
confidence: 99%
“…O padrão atual de amostras são anéis de aço inox de 100 cm³ utilizados para determinar atributos físico-hídricos do solo (Kramer et al, 2013;Guimarães et al, 2014;Fidalski;Alves, 2015;Auler;Vieira, 2017;Jardini;Amorim, 2017;Pott et al, 2017). Apesar de ser o método padrão, é recorrente o uso de ferramentas de impacto, o que certamente resulta em perturbação das condições físicas originais do solo (Souza et al, 2014), o que não ocorre nos monolitos retirados por equipamento proposto por Venzon (2014).…”
Section: Introductionunclassified